Effect of Neem Seed Kernel Extracts in the Management of Rice Stem Borers in the Field in Nigeria - Ogah, O.O.; Omoloye, A.A.; Nwilene, F.E.; Nwogbaga, A.C. (2014)
Stem borers are economic pests of rice and its management through conventionalmethods has not given the desired results. Hence in this study field experiments wereconducted to determine the comparative efficacy of neem seed kernel extracts(Azadirachta indica; (Neem) and synthetic insecticide (Carbofuradan) against ricestem borers in Nigeria during 2006/07 farming season. The effect of these sprayingswas also recorded on natural enemies and yield attributes. Results showed that thetwo pesticides significantly (p < 0.01) reduced stem borers damage (number of deadhearts, white heads) compared to untreated check, and also significantly (p < 0.05)increased number of productive tillers with resultant increase in grain yield than thecontrol plots. Maximum numbers of different natural enemies were found in neemextract treated plots against the carbofuran treated plots. It is suggested that on thebasis of infestation of borer, high yield and conservation of natural enemies, neemseed extract can be regarded as suitable alternative to synthetic insecticides for themanagement of rice stem borers in the field.